LONG-TERM FISCAL IMPLICATIONS OF AGING: THE CASE OF MOLDOVA - Prohnițchi, Valeriu (Economy and Sociology, 2024)
Moldova’s population is shrinking and aging rapidly. From the current 2.5 million, its population is expected to reach 2.2 million by the year 2030 and 1.7 million by 2040. The share of the population aged 65+ is set to rise from 16% in 2023 to 21% in 2030 and 24% in 2040. According to Moldova’s National Transfer Accounts, the elderly aged 60+ account for about 40% of the total budgetary transfers outflows and contribute 20% to the budgetary inflows. If the 2019-2022 age-specific trends in public flows prevail in the next one-and-half decade (baseline scenario), this may lead to severely negative consequences for the Moldovan public finance, with the debt-to-GDP ratio exceeding 80% by 2040. The alternative scenario, in which the deb-to-GDP ratio is allowed to rise only up to the level aligned to Maastricht convergence criteria (60%), requires a gradual growth in fiscal burden, from the current 30% to about 36% by 2040. However, considering the permanent changes in the demographic structure, maintaining debt below the sustainability threshold would involve recurrent increases in the fiscal burden, which is not economically and politically feasible. Additional gains in labor productivity and in labor participation of the working age population are therefore required to ensure long-term fiscal sustainability without eroding the economy’s competitiveness.